Speed optimization of positional electric drives using the maximum principle - Shurub, Yu.; Rudenskyi, A. (Energy and Automation, 2025)
The performance quality of many technological processes depends to a large extent on the inertial properties of executive devices. Positional electric drives with servomotors, which have integrating properties, are widely used as executive devices of automatic control systems. Optimizing the speed of such electric drives makes it possible to improve the quality of technological processes, reduce dynamic adjustment errors caused by the influence of the inertia of the executive device. The maximum principle is a convenient means of determining the optimal control law as a function of phase coordinates, that is, a means of synthesizing optimal regulators in closed systems, and a function of time, that is, a means of finding optimal software controls in open systems, which are positional electric drives with relay control. The purpose of this work is to substantiate the application of the maximum principle for the problem of optimizing the speed of positional electric drives and to find an analytical solution to this problem. Key words: optimal control, maximum principle, electric drive, optimality criterio